RANCANGAN PEMBELAJARAN TRANSFORMATIF PADA MATA KULIAH WAJIB KURIKULUM (MKWK) DAN PENCIRI UNIVERSITAS DALAM BLOK TAHAP PEMBELAJARAN BERSAMA - Dwi Purnomo; Anas Bunyamin; Wahyu Gunawan; Ida Widianingsih; Wanodyo Sulistyani; Irsan Firmansyah (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Transformative education is not negotiable. Along with the changing era, where generation Y and Z havethe character of their generations; they are very different from the previous generation. The various effects ofdigital disruption make it important in presenting transformative education. Transformative means that new waysare needed to ensure that a series of education can provide good outcomes for learning. The current challenges,embedding the character and attitude of statesmanship, critical thinking, and being able to provide creativesolutions to those around them are fundamental to producing superior learners. There are five compulsorysubjects, namely Indonesian, English, Religion, Pancasila, and Citizenship which are often still delivered inconventional ways. In this era, learning is required to produce noble values that are internalized as learners.Besides this, there are contextual things that need to be embedded in these Y and Z generation learners, especiallyin the context of changing times whose challenges are different and lead to sustainable actions that are grown togenerate benefits for their surroundings. This research was conducted with a transformative research approach,developed directly for three years at Padjadjaran University and then titrated three times so that it could producecompulsory course formulations and university characteristics that resulted in learning outcomes in the form ofmastery of values, attitudes, and basic skills needed as fundamental learners in the industrial era 4.0. This researchproduced an elaborative model of compulsory subjects and university characteristics by elaborating oncompulsory substances, skills, and attitudes with learning models designed as a unit to provide a greaterprobability of achieving outcomes.Keywords: Compulsory Courses, Industry 4.0, Generation Z, Transformative Learning